An Innovative Perioperative Pain Program for Chronic Opioid Users: An Academic Medical Center's Response to the Opioid Crisis. (January 2019) - Hanna, Marie N.; Speed, Traci J.; Shechter, Ronen; Grant, Michael C.; Sheinberg, Rosanne; Goldberg, Elizabeth; Campbell, Claudia M.; Theodore, Nicholas; Koch, Colleen G.; Williams, Kayode
Increased utilization of prescription opioids for pain management has led to a nationwide public health crisis with alarming rates of addiction and opioid-related deaths. In the surgical setting, opioid prescriptions have been implicated as a contributing factor to the opioid epidemic. The authors developed an innovative model to address aspects of pain management and opioid utilization during preoperative evaluation, acute surgical hospitalization, and postoperative follow-up for chronic opioid users. This program involves multidisciplinary teams that include acute and chronic pain specialists, psychiatrists, integrative medicine specialists, and physical medicine and rehabilitation services. It also features a novel infrastructure for triage and pain management education and treatment. Individualized patient plans are devised that can include preoperative opioid weaning, regional anesthesia that minimizes opioid use, and multimodal techniques for surgical pain treatment. Multidisciplinary programs such as this have the potential to both improve perioperative pain control and prevent escalation of opioid use among chronic opioid users.